THE INFLUENCE OF ARGUMENT QUALITY AND SOURCE CREDIBILITY IN GADGET PRODUCT REVIEW VIDEOS ON YOUTUBE TOWARD THE PERCEIVED INFORMATION USEFULNESS, INFORMATION ADOPTION, AND PURCHASE INTENTION OF GENERATION Z IN INDONESIA - Jonathan Ivan Wijaya (Journal of Social and Economics Research, 2024)
Generation Z is a generation that does not easily trust information about a product provided by a brand and they require further verification of the information through various product review videos on YouTube. Through this study, the researcher wants to find out the influence and role of argument quality in product review videos and source credibility of the YouTubers on certain channel on the perceived information usefulness, information adoption, and purchase intention of Generation Z in Indonesia, especially in the technology (gadget) industry. The researcher will use a quantitative research approach using a survey (questionnaire). A total of 267 valid respondents filled out this questionnaire with the criteria, namely Generation Z in Indonesia, who have watched gadget product review videos on the Jagat Review channel on YouTube (specifically in the last 3 months). Based on the results of the analysis, the researcher found that the argument quality in gadget product review videos and the source credibility of the tech YouTubers on certain channel have a great influence on the perceived information usefulness and information adoption of Generation Z in Indonesia, especially those who live in the Java Island area. With good perceived information usefulness and information adoption, it will easily increase the purchase intention of Generation Z in Indonesia towards the gadget products reviewed. Therefore, the researcher recommends that marketers understand the importance of argument quality and source credibility in gadget product review videos as well as collaborate with tech YouTube channels to review and promote gadget products from their companies to reach more customers from Generation Z in Indonesia. In addition, the researcher also has suggestions for the YouTube channel of Jagat Review to increase the engagement of its viewers so that more of them want to accept, adopt, and follow the various suggestions/recommendations given.